Identification of PITX3 mutations in individuals with various ocular developmental defects. (4th May 2018) - Zazo Seco, Celia; Plaisancié, Julie; Lupasco, Tatiana; Michot, Caroline; Pechmeja, Jacmine; Delanne, Julian; Cottereau, Edouard; Ayuso, Carmen; Corton, Marta; Calvas, Patrick; Ragge, Nicola; Chassaing, Nicolas
ABSTRACT: Background : Congenital cataract displays large phenotypic (syndromic and isolated cataracts) and genetic heterogeneity. Mutations in several transcription factors involved in eye development, like PITX3, have been associated with congenital cataracts and anterior segment mesenchymal disorders. Materials and methods : Targeted sequencing of 187 genes involved in ocular development was performed in 96 patients with mainly anophthalmia and microphthalmia. Additionally, Sanger sequencing analysis of PITX3 was performed on a second cohort of 32 index cases with congenital cataract and Peters anomaly and/or sclereocornea. Results : We described five families with four different PITX3 mutations, two of which were novel. In Family 1, the heterozygous recurrent c.640_656dup (p.Gly220Profs*95) mutation cosegregated with eye anomalies ranging from congenital cataract to Peters anomaly. In Family 2, the novel c.669del [p.(Leu225Trpfs*84)] mutation cosegregated with dominantly inherited eye anomalies ranging from posterior embryotoxon to congenital cataract in heterozygous carriers and congenital sclereocornea and cataract in a patient homozygous for this mutation. In Family 3, we identified the recurrent heterozygous c.640_656dup (p.Gly220Profs*95) mutation segregating with congenital cataract. In Family 4, the de novo c.582del [p.(Ile194Metfs*115)] mutation was identified in a patient with congenital cataract, microphthalmia, developmental delay and autism. In Family 5, the c.38G>A (p.Ser13Asn) mutation segregated dominantly in a family with Peters anomaly, which is a novel phenotype associated with the c.38G>A variant compared with the previously reported isolated congenital cataract. Conclusions : Our study unveils different phenotypes associated with known and novel mutations in PITX3, which will improve the genetic counselling of patients and their families.